Hidden mediator roles of university spin-offs in Triple Helix networks - Marina S. van Geenhuizen; Qing Ye; Mozhdeh Taheri (Triple Helix, 2016)
University spin-off firms contribute to bringing knowledge created at university to market. The networks these firms employ with other Triple Helix actors serve as not only getting access to resources but also shaping processes of collective learning in transforming the knowledge most adequately. In addition, spin-offs may affect the networks and behavior of network participants. While the first role has received large attention, collective learning and transforming networks and network partners have not. The paper addresses a key requirement in this setting, namely diversity in networks. We use a database of 105 young university spin-off firms and measure the socio-economic networks. A share of around 25 to 35~% of the firms tends to have an important potential mediator role, as they employ three to five different partners, connect with large firms as well as governments (outside the university), and have inserted a majority of strangers (outsiders) in their network. In the next step, to better understand partner diversity, we assess a simplified model. The level of innovativeness is found to be an important driver of diversity, with pre-start working experience (domains) and multidisciplinary education as important enabling factors. In exploring actual mediator roles using two case studies, we observe that Triple Helix actors are most diverse and tightly connected in testing activities in practice (pilots) enabling transformation of networks and network partners. The paper concludes with a summary, policy relevance, and future research paths.
Keywords: 330; Diversity; Mediator role; Networks; Spin-off firms; Triple Helix networks